2017
DOI: 10.13075/ijomeh.1896.01134
|View full text |Cite
|
Sign up to set email alerts
|

How job and family demands impact change in perceived stress: A dyadic study

Abstract: Objectives: The aim of this two-wave study has been to test the spillover and crossover of job and family demands on changes in perceived stress at work and in the family. Specifically, we proposed that demands from one domain (work or family) spilled over to another domain through interrrole conflict (work-family/family-work conflict) and context-specific self-efficacy. Additionally, we hypothesized that changes in perceived stress were impacted not only by a person's own demands through interrole conflict bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…More research is needed into explanations for this finding, but it may be hypothesized that, as mothers are culturally considered in charge of the family domain, any interferences from this domain and their consequences (in the work and family domains) may be seen –by both mothers and fathers– as underperforming in their family role. In this sense, research suggests that women experience more stress when they feel that their spouses do not meet their work expectations due to obligations they have at home (i.e., family-to-work conflict, Smoktunowicz & Cieślak 2018 ), which in turn may negatively influence the mother’s family satisfaction. In addition, a second partner association found in fathers was that a higher job satisfaction in fathers was associated with a higher family satisfaction in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed into explanations for this finding, but it may be hypothesized that, as mothers are culturally considered in charge of the family domain, any interferences from this domain and their consequences (in the work and family domains) may be seen –by both mothers and fathers– as underperforming in their family role. In this sense, research suggests that women experience more stress when they feel that their spouses do not meet their work expectations due to obligations they have at home (i.e., family-to-work conflict, Smoktunowicz & Cieślak 2018 ), which in turn may negatively influence the mother’s family satisfaction. In addition, a second partner association found in fathers was that a higher job satisfaction in fathers was associated with a higher family satisfaction in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived Stress Scale (PSS-4), and in the workplace ( Cohen et al, 1983 ; Lesage et al, 2012 ; Smoktunowicz and Cieślak, 2017 ). Consisted of four items such as e.g., “How often have you felt difficulties were piling up so high that you could not overcome them?” All items were rated on a 5-point Likert-like scale where 1 meant Never and 5 meant Almost always .…”
Section: Methodsmentioning
confidence: 99%
“…Vahedi and colleagues [ 43 ] reported that both work-family conflict and inter-parental conflict represented two potential levers for interventions to produce health benefits for the whole family system. As individuals within families continually influence one another [ 44 , 96 , 102 ], efforts to reduce stress and strain on employees and to promote work-life balance across generations could include partners as part of these interventions. Another reason why the children’s health-related quality of life did not change might be that the questionnaire was insensitive to our study changes.…”
Section: Discussionmentioning
confidence: 99%